Informática en medicina veterinaria - Hird, David; Carter, Craig (Avances en Ciencias Veterinarias, 1993)
The present and future impact of informatics in veterinary, medicine is reviewed for the areas of communications, monitoring, trade and commerce, geographic information systems, veterinary education, clinical diagnosis, artificial intelligence, laboratory diagnosis, and artificial reality. Key words: Informátics, computers, diagnóstics. Palabras claves: Informática, computadoras, diagnóstico.